Nordic lights. Work, management and welfare in Scandinavia (Stockholm, 2013)
"The Nordic experience shows that there is no trade-off between equality and economic development. These models of productive welfare and solidaristic individualism are today challenged due to global pressures and politics of deregulation and cuts in welfare. Inequalities grow. But, in spite of their international dependence, the Nordic countries have been different for a long time, and can be so also in the future. Their “provisional utopias” change as experiences grow. With this background Nordic Lights analyses how management trends like Lean, NPM, BPR, and Toyotism are adapted in the Scandinavian countries. What are the consequences for women and young workers, work environment, flexibility and unions? Do Scandinavian contributions to a decent and productive working life – like socio-technical work organisation and dialogue based management as known from Volvo – show that another world of work is possible?"